1984
DOI: 10.1080/00365518409083606
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of plasma fibronectin concentration following infusion of a gelatin-based plasma substitute in man

Abstract: Intravenous infusion of 500 ml of a gelatin-based plasma substitute, Haemaccel, given to healthy volunteers, resulted in a significant decrease of the immunoreactive plasma fibronectin concentration 48 h and 72 h after infusion. One hour after infusion, the ability of fibronectin to bind gelatin was inhibited with a gradual recovery within 48 h. A dextran based plasma substitute, Macrodex, did not have this effect on plasma fibronectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This cannot be explained by differences in haemodilution. Brodin et al studied healthy adults and found that 500 ml gelatin-based plasma substitute, HaemaccelB resulted in significant plasma fibronectin depletion 48 h and 72 h after infusion, whereas the dextran-based plasma substitute, MacrodexB, did not have this effect (16). We found the same phenomenon in our surgical patients.…”
Section: Discussionsupporting
confidence: 81%
“…This cannot be explained by differences in haemodilution. Brodin et al studied healthy adults and found that 500 ml gelatin-based plasma substitute, HaemaccelB resulted in significant plasma fibronectin depletion 48 h and 72 h after infusion, whereas the dextran-based plasma substitute, MacrodexB, did not have this effect (16). We found the same phenomenon in our surgical patients.…”
Section: Discussionsupporting
confidence: 81%
“…We previously found that the gelatin-derived plasma substitute could block the plasma opsonic activity, and in this study, we were able to demonstrate electrophoretically the interaction of this material with fibronectin. Other workers have reported a decrease in plasma fibronectin following infusion of this material (34).…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, normovolemia can be achieved when initially higher amounts of gelatin (1.5-2 times the volume loss) are infused; to maintain normovolemia, reinfusions are needed more frequently. Apart from the dilutional fall of the red cell concentration [22], it seems necessary to limit the quantity of gelatin solution that can be given because gelatin reduces the optimizing function of fibronectin [23]. Neither specific effects on the blood clotting mechanism nor antithrombotic properties of gelatins have been demonstrated (for side effects, see below).…”
Section: Gelatinmentioning
confidence: 99%